The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1631/jzus.2006.b0992
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response study of spinal hyperbaric ropivacaine for cesarean section

Abstract: Abstract:Background: Spinal hyperbaric ropivacaine may produce more predictable and reliable anesthesia than plain ropivacaine for cesarean section. The dose-response relation for spinal hyperbaric ropivacaine is undetermined. This double-blind, randomized, dose-response study determined the ED50 (50% effective dose) and ED95 (95% effective dose) of spinal hyperbaric ropivacaine for cesarean section anesthesia. Methods: Sixty parturients undergoing elective cesarean section delivery with use of combined spinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…The efficacy of intrathecal ropivacaine for regional anesthesia is mainly concluded from studies of Chinese patients undergoing cesarean section,39,40 urological surgery,41 or orthopedics surgery 11,42. Doses of ropivacaine used for spinal anesthesia have ranged from 8 to 22.5 mg, and it has been suggested that ropivacaine is less potent than bupivacaine 4345.…”
Section: Therapeutic Efficacymentioning
confidence: 99%
“…The efficacy of intrathecal ropivacaine for regional anesthesia is mainly concluded from studies of Chinese patients undergoing cesarean section,39,40 urological surgery,41 or orthopedics surgery 11,42. Doses of ropivacaine used for spinal anesthesia have ranged from 8 to 22.5 mg, and it has been suggested that ropivacaine is less potent than bupivacaine 4345.…”
Section: Therapeutic Efficacymentioning
confidence: 99%
“…Chen et al [27] performed a dose-response study of spinal hyperbaric ropivacaine in 60 parturients scheduled for elective Caesarean section. The patients were randomized to four groups and received intrathecally, using a CSE technique, 10.5, 12, 13.5 or 15 mg of hyperbaric ropivacaine following a fluid load with 1000 ml of Ringer's lactate solution.…”
Section: Introductionmentioning
confidence: 99%
“…No statistically differences between patient demographics and surgery duration were found between the three groups (table1). [4], [5], [6] .…”
Section: Methodsmentioning
confidence: 99%